2005
DOI: 10.1007/s00467-005-1955-0
|View full text |Cite
|
Sign up to set email alerts
|

The Alport nephropathy: clinicopathological correlations

Abstract: The alleged dominance of diffuse attenuation of the glomerular basement membrane (GBM) in young children and females with Alport's Syndrome (AS) suggests that it might be the initial ultrastructural manifestation of type IV collagen defects. We carried out a 'blind' review of 130 renal biopsies obtained from 100 patients with AS, emphasizing the electron microscopy changes, and related the findings to the clinical presentation and outcome. The intracapillary distribution of (1) thickened, (2) attenuated and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A large amount of protein was filtered from glomeruli and reabsorbed by renal tubular cells, contributing to renal interstitial damage. Previous studies have already demonstrated that hyperlipidemia and gross proteinuria are two crucial factors leading to renal interstitial FCs formation in some cases of glomerulonephritis [10, 14, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…A large amount of protein was filtered from glomeruli and reabsorbed by renal tubular cells, contributing to renal interstitial damage. Previous studies have already demonstrated that hyperlipidemia and gross proteinuria are two crucial factors leading to renal interstitial FCs formation in some cases of glomerulonephritis [10, 14, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…The remaining cases are autosomal recessive or autosomal dominant, caused by mutations in the genes encoding the a3 (COL4A3) or a4 chains (COL4A4) of collagen IV. New mutations may be responsible for some cases that lack family history of renal disease [1]. Hereditary nephritis is characterized clinically by persistent microhematuria, although proteinuria and renal insufficiency are commonly observed in the later stages of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The GBM is less electron dense and of variable thickness because of a complex interwoven ''basket-weave'' replication of the lamina densa. 21 There may be podocyte foot process effacement, and the epithelial aspect of the capillary wall is typically irregular. 10 Canine models of Alport syndrome have been described in Samoyed, ''Navasota,'' Doberman Pinscher, Dalmatian, and Bull Terrier dogs.…”
mentioning
confidence: 99%